PENGARUH KUALITAS LAYANAN DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN KFC - Yanuar Adi Nugroho, 09.05.51.0040; ., Farchan (Students Journal of Economic and Management, 2013)
KFC be one of [the] fast restaurant exist in competitor Indonesia closest kfc that is Mc. Donalds also fast food kind saji same and many fast foods saji of a kind then springs up. with that is KFC demanded to give what best for customer, KFC also demanded to give maximal service, products have a certain quality and variatif dish with cloth feels well, with clean place and pleasant. be seen from place location that is KFC Banyumanik has place sterategis close to housing, office complex, shopping centre, campus and road delivers regency. KFC Banyumanik want to be market lider humorously customer around, customer from city to come or even also customer that rush by. This study aimed to examine the effect of service quality and brand image to customer satisfaction case study on where to eat fast food KFC Banyumanik.Variable in this watch fulness service quality, and brand image as independent variable and customer satisfaction as variable dependen. this watchfulness population consumer kfc that presents semarang especially KFC Branch Banyumanik. watchfulness sample election technique is done random system manner, so that got sample total 100 respondents. data analysis that used to answer watchfulness hypothesis is use doubled regression analyzer, after previous done test normalitas data. besides, this watchfulness also test fit from model. test tool that with test f and determination coefficient.This watchfulness result shows that service quality, and influential brand image significant towards customer satisfaction. this watchfulness gives suggestion for KFC Banyumanik, more pay attention service quality dimension (tangible, reability, responsiveness, assurance, and empathy) besides, KFC banyumanik permanent watch over brand image so that customer KFC Banyumaik loyal permanent consumings product KFC Banyumanik.Key words: service quality, brand image, and customer satisfaction